MANAGEMENT OF RESOURCE USE IN SMALL BUSINESS AND ENTREPRENEURSHIP ACTIVITIES (Journal of Pharmaceutical Negative Results, 2022)
The use of economic resources ensures the efficiency of small business and entrepreneurship. Based on them, it will be possible to produce competitive products. In the article, on the basis of extensive theoretical and analytical material, the directions for increasing the efficiency of using the economic resources of small business and entrepreneurship are determined.